A novel histidine–tryptophan–ketoglutarate formulation ameliorates intestinal injury in a cold storage and ex vivo warm oxygenated reperfusion model in rats. Issue 5 (4th May 2020) - Chen, Zhiquan; Kebschull, Linus; Föll1, Daniel Arno; Rauen, Ursula; Hansen, Uwe; Heitplatz, Barbara; Hessler, Michael; Senninger, Norbert; Vogel, Thomas; Mohr, Annika; Becker, Felix
Abstract: Aim: The present study aims to evaluate protective effects of a novel histidine–tryptophan–ketoglutarate solution (HTK-N) and to investigate positive impacts of an additional luminal preservation route in cold storage-induced injury on rat small bowels. Methods: Male Lewis rats were utilized as donors of small bowel grafts. Vascular or vascular plus luminal preservation were conducted with HTK or HTK-N and grafts were stored at 4°C for 8 h followed by ex vivo warm oxygenated reperfusion with Krebs–Henseleit buffer for 30 min. Afterwards, intestinal tissue and portal vein effluent samples were collected for evaluation of morphological alterations, mucosal permeability and graft vitality. Results: The novel HTK-N decreased ultrastructural alterations but otherwise presented limited effect on protecting small bowel from ischemia–reperfusion injury in vascular route. However, the additional luminal preservation led to positive impacts on the integrity of intestinal mucosa and vitality of goblet cells. In addition, vascular plus luminal preservation route with HTK significantly protected the intestinal tissue from edema. Conclusion: HTK-N protected the intestinal mucosal structure and graft vitality as a luminal preservation solution. Additional luminal preservation route in cold storage was shown to be promising.